Efektivitas Budaya Organisasi dalam Mewujudkan Visi dan Misi SMA Swasta UISU Siantar - Yenni Khairani Pane; Yeni Saufina Siregar; Aman Simaremare; Ibnu Hajar; Dian Ratna Puri (Program Studi Pendidikan Biologi, 2022)
This study aims to describe the Effectiveness of Organizational Culture in Realizing the Vision and Mission of UISU Siantar Private High School. School culture is the basic personality of the school which is shaped by norms, values, beliefs, and traditions shared by school members. Because a positive school culture plays an important role in directing the behavior of school members to achieve school goals. This Research In this study, a qualitative research design was used to analyze school culture. A study that focuses on school culture, student groups or classroom behavior should use an ethnographic case study format. This study reveals that school culture has a significant impact on school effectiveness. Therefore, in implementing education reform, system leaders should emphasize the important role of school culture in school effectiveness. School improvement efforts need to be focused on the dimensions of school culture and school effectiveness. Effective planning and strategies are needed to develop working conditions in which teachers can collaborate and work together effectively. School leaders should focus on creating a positive school culture based on collaboration, and mutual support. Principals to involve all stakeholders in the formulation and development of school management strategies.